CARBON STOCK ASSESSMENT AND SOIL CARBON MANAGEMENT IN AGRICULTURAL LAND-USES IN THAILAND - Gnanavelrajah, N.; Shrestha, R.P.; Schmidt-Vogt, D.; Samarakoon, L. (John Wiley & Sons, Ltd., 2007)
The organic carbon pool in agricultural land-uses is capable of enhancing agricultural sustainability and serving as a potential sink of atmospheric carbon dioxide. A study was carried out to estimate and map carbon stock of different agricultural land-uses in a sub-watershed of Thailand and to assess the land-use sustainability with respect to carbon management. A quadrat sampling methodology was adopted to estimate the biomass and its carbon content of 11 different land-uses in the study area. Existing soil data were used to calculate the soil carbon. GIS was used for integrating biomass carbon, soil carbon and carbon stock mapping. Roth carbon model was used to project the soil carbon of present land-uses in the coming 10 years and based on which the sustainability of land-uses was predicted. The total carbon stock of agricultural land-uses was estimated to be 20 5 Tg, of which 41 49 per cent was biomass carbon and 58 51 per cent was soil carbon. Among the land-uses, para rubber had the highest average biomass C (136 34MgC ha 1) while paddy had the lowest (7 08MgC ha 1). About four-fifths of agricultural land-uses in the watershed are sustainable in maintaining the desired level of soil carbon in coming 10 years while one-fifths are unstable. Such information on carbon stock could be valuable to develop viable land-use options for agricultural sustainability and carbon sequestration.
Keywords: biomass; modelling; carbon stock; agricultural sustainability; land-use; Thailand